PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN PENELITIAN DAN PENGEMBANGAN PROVINSI SUMATERA BARAT - Aminar Sutra Dewi; Rahma Yuvika (Jurnal Bina Bangsa Ekonomika, 2022)
This study aims to test the motivation on employee performance, to test the work environment on employee performance, this research was conducted at the Research and Development Agency of West Sumatra Province. The sampling method used a total saturated sampling of 31 samples. The data analysis techniques used were validity, reliability, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. The results showed that motivation had a positive and significant effect on employee performance. And the work environment has a positive and significant effect on employee performance. So it can be concluded that the motivation is accepted and the work environment is accepted